Graph-based conflict rectification using stroke gesture approach in timetabling system (CORECTS) - Yong, Tien Fui; Choo, Wou Onn; Chue, Wen Yeen; Kok, Hui Meian (2010)
In this paper, the proposed system, CORECTS, is specially designed and developed to check if conflicts exist within planned timetable. Although this problem seems simple at first glance, it is actually quite complex to resolve it if the conflicts are not presented clearly to the schedule planner.Thus, a special graphical user interface is designed to make the entire system being more efficient to deal with conflicts when detected. CORECTS will apply a hybrid method using annealing graph algorithm and the proposed STAR-quadrants to display the conflict detection of the entire timetable.Simple stroke gesture is used to expedite the conflict resolution process. CORECTS is aimed to ease the work of the user, not just by making timetable planning more interesting, but also making some tedious configuration works faster and thus improves efficiency.